1799 Conn. Acts 511 - (:unkn) unknown (My University, 1799)
Imposed fines for non-appearance of militia muster and deficiencies of Arms, An Act For The Militia, § 4: Ammunition, and Accoutrements. Violators of non-appearance as NCOs, drummers, fifers, or trumpeters at three dollars for each day's battalion or regiment exercise. The same fined at one dollar and fifty cents for company exercise and inspection. Privates fined at two dollars for non-appearance on days of regimental or battalion exercises. For neglect, privates fined at one dollar per day. For deficiencies in each gun or pair of pistol, violators fined seventy-five cents. For deficiencies in each sword, bayonets, or cartridge boxes, violators fined fifty cents.For other articles required by law, violators fined twenty-five cents.
Keywords: MILITIAS